Time of detasseling and defoliation effect on hybrid sweet corn (Zea mays saccharata. Sturt) seed production - Rahmawati, Dwi; Rahayu, Sri; Sjamsijah, Nurul; Nafisah, Siti (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: Sweet corn (Zea mays saccharata Sturt) is one of the horticultural crops that is in great demand in Indonesia because of its distinctive sweet taste and relatively short production time. To improve the quality and quantity of hybrid sweet corn seed production, it is necessary to apply appropriate agronomic techniques, such as detasseling (removal of male flowers) and defoliation (pruning leaves). This study aims to determine the interaction between detasseling time and the number of leaves pruned on the production parameters of hybrid sweet corn. Methods: The study was conducted in Wringintelu Village, Puger, Jember, from August to December 2022, using a factorial randomized block design (RBD) with three replications. The treatments consisted of three detasseling times (48 DAP, 50 DAP, and 52 DAP) and three levels of defoliation (no defoliation, 2 leaves, and 4 leaves). Data were analyzed using ANOVA and continued with a 5% DMRT test if there was a significant effect. Results: The results showed that the interaction of detasseling time of 48 HST with 4-leaf defoliation gave the best results on the parameters of cob weight (78.55 g) and cob length (14.97 cm). Individually, the treatment of detasseling time of 48 HST produced the highest seed production per hectare of 18.44 tons, while 4-leaf defoliation produced a production of 18.17 tons per hectare. Conclusion: In conclusion, the combination of detasseling time of 48 HST and 4-leaf defoliation is the best treatment to increase the production of hybrid sweet corn seeds, so it can be a recommendation for agronomic practices to increase sweet corn productivity in Indonesia.